The European Central Bank - Michael Binder; Volker Wieland (Goethe University Frankfurt, Center for Financial Studies (CFS), 2006)
The establishment of the ECB and with it the launch of the euro has arguably been a unique endeavor in economic history, representing an important experiment in central banking. This note aims to summarize some of the main lessons learned from this experiment and sketch some of the prospects for the ECB. It is written for /The New Palgrave Dictionary of Economics/, 2nd edition.
urn:nbn:de:hebis:30-38126
Keywords: E52; E58; 330; Central Banking; European Central Bank; Euro; Monetary Union; Zentralbank; Europäische Wirtschafts- und Währungsunion; EU-Staaten